MIĘDZY GONZO A DOKUMENTEM HISTORYCZNYM. O STATUSIE GENOLOGICZNYM REPORTAŻU ЗВІТ ЗА СЕРПЕНЬ’14 ANDRIJA SOWY (PŁOCHISZA) - Kupidura, Ryszard (Studia Ukrainica Posnaniensia, 2020)
The urgency of this paper is conditioned by the importance for the Ukrainian literary process of examining the peculiarities of literary works devoted to the Russian-Ukrainian war (2014–?). In the article, the author reviews the genre status of Andriy Sova’s Zvit za serpen ‘14. The research indicates the syncretic character of Sova’s reportage and reconstructs the social and cultural conditions for the creation of the text. In addition, the author draws attention to the language of reportage (idiostyle), which is saturated not only with emotions, but also with technical and military terminology. It was found that Zvit za serpen ‘14 contains a specific chronotope conditioned by the dynamics of events in 2014. Another important aim of the research was to investigate how Sova strengthens the reference pact with the reader. As a result, it was recognized that Sova’s strategy is to declare the truth (“I am describing only what I have seen”), frequent quoting of other soldiers, as well as posting photos, which strengthens the documentary character of the book.